Nutritional, chemical and antioxidant evaluation of Armuna lentil (Lens culinaris spp): Influence of season and soil - Liberal, Ângela (2022)
Lentils (Lens culinaris spp.) are a type of edible pulse consumed and produced worldwide; they are known for their valuable nutritional assets. The nutritional and chemical profiles of 34 Armun tilde a lentil samples were assessed together with their antioxidant capacity. In addition, the influence of both the climatic conditions during the growing season and the soil type in which they grow (Luvisol and Cambisol) on nutritional and chemical profiles was also evaluated. Our results showed large amounts of valuable nutrients, such as carbohydrates, of which approximately 47.06 % and 29.11 % consist of fibers and starch respectively and significant amounts of proteins (20.47 to 25.56 g/100 g fw) and ashes. Sucrose stood out as the main free sugar in this variety, and oxalic and gamma-tocopherol as the main organic acid and tocopherol isoform respectively. Fatty acid assessment showed the prevalence of PUFAs (45.3 to 63.7 %). A high antioxidant capacity (TBARS and OxHLIA) was also observed. Our results indicate that the growing season has a significant impact on the major nutrients in lentils such as the concentration of fat, ashes, fibers, and fructose and to a lesser extent proteins and sucrose. In addition, the two different soil types in this study do not seem to affect any of the parameters analyzed.